Diversification using assortment of local varieties of red wines - Emil Rusu; Leonora Obada; Boris Gaina; Olga Grosu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The assortment of winesproduced in Moldova iscurrently dominated by cosmopolitan varieties, mainly of the French. Global wine market study hasshownthat consumers are more attracted to wine-surprise, unknown. In this context many countrie shave resorted to valorisation of indigenous varieties and new varieties of selection. Since ancient times an assortment of vine varieties adapted to local conditions has been created in Moldova. Unfortunately, in the the 40's and 50's of last century, whith the collectivization was emphasized on European varieties spreading, local varieties being forgotten. Takinginto account all mentioned, research of 13 local red varieties for industrial purposes have started. In terms of microvinification according to classical technology, experimental wines were produced, the organoleptic, physico-chemical composition, including content phenolic compounds and anthocyanins profile were determined. Methods for analysis recommended by the OIV were used and the profile of anthocyanins in wine samples studied using high performance liquid chromatography method (HPLC) was determined. The research results showed that the dry red wines made from indigenous varieties are distinguished by different content in phenolic substances and anthocyanins. On the researche basis 4 grape varieties (Feteascæa neagræa, Rara neagræa, Negru de Cæauðseni and Codrinschi) for quality dry red wines producin gwere recommended.
Keywords: 330; local varieties; anthocyanins; phenolic compounds; physico-chemical composition; anthocyanin profile